Diagnosis, course and management of hypersensitivity pneumonitis - Hamblin, Mark; Prosch, Helmut; Vašáková, Martina (European respiratory review, 2022)
Hypersensitivity pneumonitis (HP) is a complex and heterogeneous interstitial lung disease (ILD) that occurs when susceptible individuals develop an exaggerated immune response to an inhaled antigen. In this review, we discuss the latest guidelines for the diagnostic evaluation of patients with suspected HP, the importance of identifying patients with fibrotic and progressive disease, and the evidence supporting the drugs commonly used in the treatment of HP. Differential diagnosis of HP can be challenging and requires a thorough exposure history, multidisciplinary discussion of clinical and radiologic data, and, in some cases, assessment of bronchoalveolar lavage lymphocytosis and histopathologic findings. Patients with HP may be categorised as having non-fibrotic or fibrotic HP. The presence of fibrosis is associated with worse outcomes. A proportion of patients with fibrotic HP develop a progressive phenotype, characterised by worsening fibrosis, decline in lung function and early mortality. There are no established guidelines for the treatment of HP. Antigen avoidance should be implemented wherever possible. Immunosuppressants are commonly used in patients with HP but have not been shown to slow the worsening of fibrotic disease. Nintedanib, a tyrosine kinase inhibitor, has been approved by the US Food and Drug Administration for slowing the progression of chronic fibrosing ILDs with a progressive phenotype, including progressive fibrotic HP. Non-pharmacological interventions, such as oxygen therapy, pulmonary rehabilitation and supportive care, may be important components of the overall care of patients with progressive HP.
Keywords: Fibrosis; Lung Diseases, Interstitial; United States; Alveolitis, Extrinsic Allergic; inhibitory proteinkinas; lidé; Diagnosis, Differential; Spojené státy americké; intersticiální plicní nemoci; Humans; hypersenzitivní pneumonitida; diferenciální diagnóza; fibróza; Protein Kinase Inhibitors